Informality and the playing field in Vietnam's business sector - Tenev, Stoyan; Carlier, Amanda; Chaudry, Omar; Nguyen Quynh-Tang; The World Bank; International Finnance Corporation (Washington, D.C.: World Bank and the International Finance Corporation, 2003)
The study provides evidence of the significant improvements that have taken place in Vietnamese business environment.
Includes bibliographical references
osa 27/09/2016
Loans
Keywords: Informal sector (Economics); Economic development; Vietnam -- Economic conditions -- 21st century; Business enterprises -- Vietnam; Vietnam